Pengembangan Media LKPD Berbasis Self-Regulation untuk Siswa Sekolah Dasar - Putri, Sofi Andini Julia; Istiq’faroh, Nurul; Rahma, Echa Yulia (CV. Kurnia Grup, 2026)
Self-regulation skills are a crucial component of independent learning for elementary school students, yet many students still face difficulties in managing emotions when encountering academic challenges. This research aims to develop and test the feasibility of a self-regulation-based Student Worksheet (LKPD) utilizing the Independent Emotion Regulation (REM) strategy for fifth-grade elementary school students. The research method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate), limited to the Develop stage. Data were collected through practitioner expert validation instruments and student response questionnaires. The results indicated that the